A Review of the Relationship between Psychological Capital and Psychological Well-being - Adibah Abdul Kadir (Journal of Humanistic, Management and Social Science Review, 2024)
This article uses the literature review approach to examine the current state of this topic based on the literature on the relationship between psychological capital and well-being. This article presents different definitions of psychological well-being and psychological capital proposed by different scholars, as well as information on how to build and value psychological capital and how it affects psychological well-being for the benefit of individuals and organizations. It is based on a comparative analysis of pertinent literature. Additionally, it summarizes the results of previous studies on the connection between psychological capital and psychological well-being.